(3GdKhQI GdLRGFQjI (B:s (3aj YGegG GdChd (B/s - (3eMeO GdYQHj, GdRHjQjs ([(3Ohf ecGf(B] :s (3OGQ GdHMK ,s, 1984)
(3jOhQ eMhQ GdcJGH Mhd MbjbI GdeSJbGI ef GahGg KhGQ eLGgOjf dG RGdh Ydi bjO GdMjGI h ef hKGAb fLJ ef GjOj GdeJYeQjf h GdLdGOjf h GdZGUHjfs
Keywords: (3GdKhQI GdLRGFQjIs